Idiopathic Hypoparathyroidism: Still a Diagnostic Conundrum – A Tertiary Centre Experience - Jain, Rujul; Singh, S. K.; Agrawal, N. K. (Hormone and Metabolic Research, 2020)
Idiopathic hypoparathyroidism leads to hypocalcemia and hyperphosphatasemia and usually has a genetic aetiology. The variable but often subtle signs and symptoms usually lead to a misdiagnosis of hypoparathyroidism. Case records of 32 patients of idiopathic hypoparathyroidism admitted over a period of five years were analysed. There was a lag period of 5.94 years from the onset of symptoms to the diagnosis. Carpopedal spasm was the most common indication for admission to the hospital. Trivial symptoms such as fatigue (84%) and paresthesia (62.5%) were the most common reported symptoms. A sum of 46.5% of the patients were on antiepileptic drugs before the correct diagnosis of hypoparathyroidism was made. This observation emphasized that Calcium profile should be obtained in patients with history of paresthesia and seizure to avoid the long delay in diagnosis of hypoparathyroidism.
Keywords: paraesthesia; misdiagnosis; carpopedal spasm